Glucagon increases energy expenditure independently of brown adipose tissue activation in humans. Issue 1 (20th November 2015) - Salem, V.; Izzi‐Engbeaya, C.; Coello, C.; Thomas, D. B.; Chambers, E. S.; Comninos, A. N.; Buckley, A.; Win, Z.; Al‐Nahhas, A.; Rabiner, E. A.; Gunn, R. N.; Budge, H.; et al.
Abstract : Aims: To investigate, for a given energy expenditure (EE) rise, the differential effects of glucagon infusion and cold exposure on brown adipose tissue (BAT) activation in humans. Methods: Indirect calorimetry and supraclavicular thermography was performed in 11 healthy male volunteers before and after: cold exposure; glucagon infusion (at 23 °C); and vehicle infusion (at 23 °C). All volunteers underwent 18 F‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography (PET)/CT scanning with cold exposure. Subjects with cold‐induced BAT activation on 18 F‐FDG PET/CT (n = 8) underwent a randomly allocated second 18 F‐FDG PET/CT scan (at 23 °C), either with glucagon infusion (n = 4) or vehicle infusion (n = 4). Results: We observed that EE increased by 14% after cold exposure and by 15% after glucagon infusion (50 ng/kg/min; p < 0.05 vs control for both). Cold exposure produced an increase in neck temperature (+0.44 °C; p < 0.001 vs control), but glucagon infusion did not alter neck temperature. In subjects with a cold‐induced increase in the metabolic activity of supraclavicular BAT on 18 F‐FDG PET/CT, a significant rise in the metabolic activity of BAT after glucagon infusion was not detected. Cold exposure increased sympathetic activation, as measured by circulating norepinephrine levels, but glucagon infusion did not. Conclusions: Glucagon increases EE by a similar magnitude compared with cold activation, but independently of BAT thermogenesis. This finding is of importance for the development of safe treatments for obesity through upregulation of EE.